1982
DOI: 10.1002/bip.360210214
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of pectic acid. I. Thermodynamic evidence of a pH‐induced conformational transition in aqueous solution

Abstract: SynopsisOn the basis of measurements of enthalpy of dissociation and of dilution, an intramolecular conformational transition induced by pH change is shown for pectic acid in aqueous solution. Additional evidence is given by potentiometic, viscometric, and chiroptical results. The transition from a more rigid, probably H-bonded, structure prevailing at low pH to a more extended one at around neutrality is accompanied by a AH value of about 500 cal/equiv and a AS value of 1.6 cal/equiv K in water at 25OC. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…However, if (pH -pK a ) g 2, we can assume complete ionization, i.e., no charge mobility. This is nearly the case for pectin, for which literature values of pK a vary from 4.0 to 4.4 in pure water, and from 3.5 to 4.0 at I ) 0.05 M. For pectin, pH c values ranged from 5.9 to 4.4, such that the condition (pH -pK a ) g 2 is satisfied at I e 0.1 M. 42 Conflicting values are found for the pK a of HA: Cleland 43 reported 2.8 < pK a < 3.2, depending on I and R; a more recent report gives pK a , in I ) 0.05 M, as 3.5 ( 0.1 independent of R, 44 but these values are also low enough to assume full ionization for HA over most of the pH c range. Therefore, the condition (pH -pK a ) g 2 was satisfied at I e 0.15 M. On the other hand, the larger values of pK a for PAA result in R at pH c ranging from 0.75 to 0.50 as I increases from 0.01 to 0.6 M. Despite this complication of determining the degree of charge for PAA at different condi- tions, we focus in this section on PAA because resolving effects of charge from chain stiffness for HA and pectin is even more problematic.…”
Section: Resultsmentioning
confidence: 83%
“…However, if (pH -pK a ) g 2, we can assume complete ionization, i.e., no charge mobility. This is nearly the case for pectin, for which literature values of pK a vary from 4.0 to 4.4 in pure water, and from 3.5 to 4.0 at I ) 0.05 M. For pectin, pH c values ranged from 5.9 to 4.4, such that the condition (pH -pK a ) g 2 is satisfied at I e 0.1 M. 42 Conflicting values are found for the pK a of HA: Cleland 43 reported 2.8 < pK a < 3.2, depending on I and R; a more recent report gives pK a , in I ) 0.05 M, as 3.5 ( 0.1 independent of R, 44 but these values are also low enough to assume full ionization for HA over most of the pH c range. Therefore, the condition (pH -pK a ) g 2 was satisfied at I e 0.15 M. On the other hand, the larger values of pK a for PAA result in R at pH c ranging from 0.75 to 0.50 as I increases from 0.01 to 0.6 M. Despite this complication of determining the degree of charge for PAA at different condi- tions, we focus in this section on PAA because resolving effects of charge from chain stiffness for HA and pectin is even more problematic.…”
Section: Resultsmentioning
confidence: 83%
“…The lack of interaction at neutral pH cannot be ascribed to different protonation of positive residues (Arg and Lys) of PGIP or carboxylic groups of PGA. It is possible instead that a conformational transition of the PGA structure occurs and increases the pH, creating a charge distribution not suitable for PGIP binding (Cesaro et al, 1982). Indeed, we have observed by circular dichroism analysis that PGA at pH 7.0 in the presence of 100 mM calcium is subjected to a conformational change with respect to the form present at pH 5.0 (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…[21] The ordered conformation was indicated as a rather rigid one, also on the basis of an accompanying relative increase of viscosity. The recent calculations of Benegas et al, [22] based upon the analysis of the pH titration of PA, confirmed the existence of such a transition, providing a relative increase of the stiffness parameter k from 0.1 (disordered) to 0.3 kcal Á mol À1 Á Å À2 for the helical conformation.…”
Section: Resultsmentioning
confidence: 99%